The Effects of Satisfaction of Basic Psychological Needs at School on Children’s Prosocial Behavior and Antisocial Behavior: The Mediating Role of School Satisfaction - Tian, Lili; Zhang, Xiao; Huebner, E. Scott (Frontiers in Psychology, 2018)
Grounded in Basic Psychological Need Theory (BPNT), we examined the direct effects of the satisfaction of three basic psychological needs at school (i.e., satisfaction of autonomy needs at school, satisfaction of relatedness needs at school, and satisfaction of competence needs at school) on prosocial behavior and antisocial behavior as well as the mediation effects of school satisfaction on the relations between the satisfaction of three basic psychological needs at school and prosocial behavior as well as antisocial behavior. We employed a sample of 801 Chinese children (429 males; Mage=9.47) in a 3-wave longitudinal study, with each wave occurring six months apart. Direct and indirect effects were estimated by Structural Equation Modeling. Results indicated that: (1) Satisfaction of relatedness needs at school and competence needs at school, but not satisfaction of autonomy needs at school, displayed direct effects on prosocial behavior. Also, satisfaction of relatedness needs at school, but not satisfaction of autonomy needs at school or competence needs at school, displayed direct effects on antisocial behavior. (2) Both satisfaction of relatedness needs at school and competence needs at school displayed indirect effects on prosocial behavior and antisocial behavior via school satisfaction as a mediator. However, satisfaction of autonomy needs at school failed to have indirect effects on prosocial behavior or antisocial behavior via school satisfaction. These findings suggest differential predictors of children’s prosocial and antisocial behavior, supporting the separability of the two constructs. The findings also suggest developmental differences in need satisfaction, with the satisfaction of autonomy needs playing a relatively less important role in school-age children. We also discussed limitations and practical applications of the study.